PERAN PEMBELAJARAN IPAS PADA SISWA KELAS V SDN KLAMPIS 02 UNTUK MENCIPTAKAN GENERASI PEDULI LINGKUNGAN - Vania Hayunanda; Ine Sukma Permatasari; Sindi Pusparani; Didik Tri Setiyoko (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Environmental issues have become a major concern due to various human activities that disrupt ecosystem balance. This study aims to explore the role of Social and Natural Sciences (IPAS) learning in fostering environmental awareness among fifth-grade students at SDN Klampis 02. The research employed a descriptive qualitative approach using systematic literature review methods to analyze data from various sources. The findings revealed that project-based, collaborative, and context-driven IPAS learning effectively enhanced students' awareness of the importance of environmental preservation. Activities such as direct observation, recycling projects, and group discussions successfully encouraged student engagement in environmental issues. Despite challenges like limited facilities and initial awareness, support from teachers, parents, and school principals significantly contributed to successful implementation. This study highlights the importance of IPAS learning as a means to instill environmental values in students from an early age.